DEVELOPMENT OF STATISTIC'S TEACHING AIDS ON MEAN, MEDIAN, MODUS TOPIC FOR SIXTH GRADE ELEMENTARY SCHOOL STUDENTS - Endang Sri Agustini; M Arman Putra Karwana; M Rizky Ramandani; Winda Putri Yulianti; Zulkardi Zulkardi; Hapizah Hapizah; Budi Mulyono; Meryansumayeka Meryansumayeka (PEDAGOGIA, 2022)
This study aims to develop a statistical teaching aid that is valid, effective, and practical on the material of Mean, Median, and Mode of Class VI Elementary School students. The development was carried out using the ADDIE (Implementation, Design, Development, Implementation, Evaluation) method, and the data was collected through observation and interviews, which were then analyzed descriptively. This article starts with how to make and test the props, which then comes to the part where the props made are by the original purpose of making the props and by the characteristics of good teaching aids. The validity of the teaching aids is based on the validator's assessment. For effectiveness, it is assessed from the results of students working on solutions about the Mean, Median, and Mode using the Statistics Board Teaching Aid. At the same time, practicality is known from the trial results to find out the difficulties experienced by students. The study results indicate that the Statistics Board is a valid, efficient, and practical money-teaching tool. The study results indicate that the Statistics Board is a valid, efficient, and practical teaching aid.